Time-based prospective memory functioning in mild cognitive impairment associated with Parkinson’s disease: relationship with autonomous management of daily living commitments - Costa, Alberto; Zabberoni, Silvia; Peppe, Antonella; Serafini, Francesca; Scalici, Francesco; Caltagirone, Carlo; Carlesimo, Giovanni Augusto (Frontiers in Human Neuroscience, 2015)
Objective. Prospective memory (PM), that is, the ability to keep in memory and carry out intentions in the future, is reported to be impaired in individuals with Parkinson's disease (PD). PM failure may be also associated with reduced daily living functioning in these patients. Little is known, however, about the relationship between mild cognitive impairment (MCI) and time-based PM functioning in PD patients and the possible impact of PM deficits on patients' autonomy in daily living. Here we aimed to investigate whether MCI associated with PD affects time-based PM. We also wished to determine whether PM impairment accounts for reduced autonomous management of medication in these patients. Method. The study included 48 PD patients with MCI, 33 PD patients without cognitive disorders (PDN) and 20 healthy controls. The time-based PM procedure required that subjects perform an action after a fixed time. The PM procedure was incorporated in the standard neuropsychological assessment. One score was computed for the ability to retrieve the intention (prospective component) and one for remembering the action to be executed (retrospective component). The Pill Questionnaire was administered to assess the ability to manage medication. Results. PD patients with MCI performed less accurately in the PM procedure than HC and tended to perform poorer than PDN. Moreover, in PD patients with MCI, accuracy on the prospective component of the PM task and performance on the Modified Card Sorting Test significantly predicted the ability to manage medication. Conclusions. Results document that reduced efficiency of time-based PM processes in PD is specifically related to the presence of MCI. The same data indicate that PM weakness may be associated with impaired daily living functioning and decreased autonomy.